The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1159/000091060
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Efficacy of Fluoride Toothpastes Assessed with pH Cycling

Abstract: This study addressed the dose response between fluoride toothpastes and in vitro de- and remineralization, to predict the efficacy of toothpastes and understand the mode of action in the range 0–3,000 ppm F. Enamel lesions were pH-cycled with calcium uptake and loss being assessed daily. Both ‘shallow’ (about 50 µm deep) and ‘deep’ (about 200 µm deep) lesions were studied. F treatments were given in 30 (w/v)% toothpaste dilutions for up to 5 min daily. Calcium loss during the demineralization periods showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 40 publications
3
45
2
4
Order By: Relevance
“…The results of the current study are in accordance with ten Cate et al 22 who found that when shallow ('early') lesions were studied the predominant effect of fluoride was to inhibit demineralisation up to 50% in the 'classical' fluoride range 0-1,500 ppm, and this increased to 70% when 3,000 ppm F -pastes were given. The results of the current study indicated that ozone alone has a minimal effect but this was enhanced when fluoride containing products were used in combination with use of ozone and this is in agreement with recently published study that also disputed the efficacy of ozone without its constituent adjunct therapies.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the current study are in accordance with ten Cate et al 22 who found that when shallow ('early') lesions were studied the predominant effect of fluoride was to inhibit demineralisation up to 50% in the 'classical' fluoride range 0-1,500 ppm, and this increased to 70% when 3,000 ppm F -pastes were given. The results of the current study indicated that ozone alone has a minimal effect but this was enhanced when fluoride containing products were used in combination with use of ozone and this is in agreement with recently published study that also disputed the efficacy of ozone without its constituent adjunct therapies.…”
Section: Discussionsupporting
confidence: 92%
“…Besides, as in the natural caries process, in the present model demineralizing challenges were followed by remineralizing phases, allowing the fluoride ion to have an effect on both phases. Both the number of demineralization phases (6× demin/day) as well as the total demineralization time per day (4 h/day) was similar to other pHcycling studies [38,39]. These conditions resulted in subsurface initial caries lesions showing net demineralization in our pilot tests (data not shown), so this model fulfilled the conditions intended to be simulated.…”
Section: Figsupporting
confidence: 81%
“…The use of bovine enamel has been verified in a number of in vitro studies to evaluate the effect of anticariogenic agents on enhancing enamel remineralization and inhibiting enamel demineralization. 22 Using the in situ model, human and bovine enamel have shown similar characteristics in subsurface lesion remineralization under irradiation or abrasion influence. 23 However, bovine enamel is not similar to human enamel in some aspects; for example, it may have a higher porosity, 24 potentially leading to a faster demineralization rate.…”
Section: Discussionmentioning
confidence: 98%